The trends of potential user research from 2014-2023 based on bibliometric and BERTopic - Kun, Liu; Alli, Hassan; Abd Rahman, Khairul Aidil Azlin (Associacao Nacional de Pos-Graduacao e Pesquisa em Administracao, 2024)
Objective: Despite the increasing importance of lead generation research in increasing product or market share, cost and resource constraints have become a challenge for SMEs.Therefore, this study aims to explore and reveal research themes and market trends hidden in articles on lead generation over the past 10 years. . Theoretical Framework: In this study, qualitative and quantitative methods are combined, and three methods of bibliometrics, network analysis and BERTopic topic modeling are used to analyze the literature. Method: A total of 7446 articles were analysed using bibliometrics, network analysis and BERTopic thematic modelling as the basis of a mixed method approach. Results and Discussion: The study found that the field is currently experiencing a downward trend after a phase of rapid growth. During this period, the United States and China were the countries with the highest number of articles accounting for 77% of the total; the Journal of Cleaner Journal of Cleaner Production was the most cited journal. In addition, the potential user studies cover 43 mainstream topics, focusing on 6 aspects . In the in-depth analysis of the theme evolution, it was found that the potential user study gradually evolved from the initial multidimensional application to focus on open service, and was more oriented towards the public service field. Research Implications: This provides a strong theoretical basis and practical guidance for identifying potential customers and increasing conversion rates and revenues. Originality/Value: To our knowledge, this is the first study to use a mixed-methods approach to lead generation, which will help researchers to tackle more complex challenges and changes in the future.